2022
DOI: 10.3390/toxics10120751
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Hydroxylated and Methoxylated Brominated Diphenyl Ethers in Marine Environments

Abstract: Hydroxylated polybrominated diphenyl ethers (OH-PBDEs) and methoxylated polybrominated diphenyl ethers (MeO-PBDEs) are present in the marine environment worldwide. Both OH-PBDEs and MeO-PBDEs are known natural products, whereas OH-PBDEs may also be metabolites of PBDEs. There is growing concern regarding OH-PBDEs as these compounds seem to be biological active than PBDEs. In the present study, we reviewed the available data on the contamination of OH/MeO-PBDEs in the marine environment worldwide, including sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 83 publications
(130 reference statements)
0
7
0
Order By: Relevance
“…Two MeO-penta-BDE isomers in porpoise and dolphin samples with RTs of 8.23 and 10.47 min were screened using their [M – Br + O] − fragment with diagnostic ions of 528.7127 (C 13 H 7 79 Br 3 81 BrO 3 − ; mass error = 2.6 ppm), 530.7103 (C 13 H 7 79 Br 2 81 Br 2 O 3 − ; mass error = 1.8 ppm), and 532.7075 (C 13 H 7 79 Br 81 Br 3 O 3 − ; mass error = 0.5 ppm) with isotope intensity ratios of 69:100:65. MeO- and OH-BDEs are not manufactured; however, they can be naturally formed in marine organisms. , It was reported that OH-BDEs did not biomagnify in the marine food web, and OH-BDEs in marine mammals mainly originate from (1) metabolism of PBDEs and/or MeO-BDEs and (2) the direct uptake from the natural source. A significant positive correlation was found between concentrations of OH-tetra-BDE and BDE-47/MeO-tetra-BDE in both porpoises and dolphins ( p < 0.05; Table S6), suggesting that the indirect source (i.e., metabolism of PBDEs and/or MeO-BDEs) could be the main origin for OH-tetra-BDE in the investigated cetaceans. MeO-BDEs were reported to have biomagnification potential, and MeO-BDEs present in marine mammals were generally considered to come from natural sources. Nevertheless, a significant positive correlation was observed between concentrations of MeO-BDEs and native PBDEs in both porpoises and dolphins ( p < 0.05; Table S6), indicating the possible contribution of the biotransformation of PBDEs to MeO-BDEs in the investigated marine mammals.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Two MeO-penta-BDE isomers in porpoise and dolphin samples with RTs of 8.23 and 10.47 min were screened using their [M – Br + O] − fragment with diagnostic ions of 528.7127 (C 13 H 7 79 Br 3 81 BrO 3 − ; mass error = 2.6 ppm), 530.7103 (C 13 H 7 79 Br 2 81 Br 2 O 3 − ; mass error = 1.8 ppm), and 532.7075 (C 13 H 7 79 Br 81 Br 3 O 3 − ; mass error = 0.5 ppm) with isotope intensity ratios of 69:100:65. MeO- and OH-BDEs are not manufactured; however, they can be naturally formed in marine organisms. , It was reported that OH-BDEs did not biomagnify in the marine food web, and OH-BDEs in marine mammals mainly originate from (1) metabolism of PBDEs and/or MeO-BDEs and (2) the direct uptake from the natural source. A significant positive correlation was found between concentrations of OH-tetra-BDE and BDE-47/MeO-tetra-BDE in both porpoises and dolphins ( p < 0.05; Table S6), suggesting that the indirect source (i.e., metabolism of PBDEs and/or MeO-BDEs) could be the main origin for OH-tetra-BDE in the investigated cetaceans. MeO-BDEs were reported to have biomagnification potential, and MeO-BDEs present in marine mammals were generally considered to come from natural sources. Nevertheless, a significant positive correlation was observed between concentrations of MeO-BDEs and native PBDEs in both porpoises and dolphins ( p < 0.05; Table S6), indicating the possible contribution of the biotransformation of PBDEs to MeO-BDEs in the investigated marine mammals.…”
Section: Resultsmentioning
confidence: 93%
“…MeO- and OH-BDEs are not manufactured; however, they can be naturally formed in marine organisms. , It was reported that OH-BDEs did not biomagnify in the marine food web, and OH-BDEs in marine mammals mainly originate from (1) metabolism of PBDEs and/or MeO-BDEs and (2) the direct uptake from the natural source. A significant positive correlation was found between concentrations of OH-tetra-BDE and BDE-47/MeO-tetra-BDE in both porpoises and dolphins ( p < 0.05; Table S6), suggesting that the indirect source (i.e., metabolism of PBDEs and/or MeO-BDEs) could be the main origin for OH-tetra-BDE in the investigated cetaceans. MeO-BDEs were reported to have biomagnification potential, and MeO-BDEs present in marine mammals were generally considered to come from natural sources. Nevertheless, a significant positive correlation was observed between concentrations of MeO-BDEs and native PBDEs in both porpoises and dolphins ( p < 0.05; Table S6), indicating the possible contribution of the biotransformation of PBDEs to MeO-BDEs in the investigated marine mammals. The origin of MeO-BDEs in marine cetaceans is likely to be attributed to both natural source and PBDE metabolism, which deserves future investigation.…”
Section: Resultsmentioning
confidence: 93%
“…For instance, OH-PBDEs were found to bioaccumulate less likely than PBDEs or MeO-BDEs. 43 Likewise, OH-PCBs were only detected in the plasma but not the blubber of harbor seals ( Phoca vitulina ). 44 Also, the present sample cleanup method (and assumedly others as well) does not cover hydroxylated compounds such as bromophenols, which require a more polar solvent for their elution ( section 2.3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this context it is important to note that the high amounts of a hydroxylated polyhalogenated compound in the blubber of marine mammals were surprising. For instance, OH-PBDEs were found to bioaccumulate less likely than PBDEs or MeO-BDEs . Likewise, OH-PCBs were only detected in the plasma but not the blubber of harbor seals ( Phoca vitulina ) .…”
Section: Resultsmentioning
confidence: 99%
“…Agarwal et al [ 11 ] reported marine bacteria as producers of OH-PBDEs and established a genetic and molecular foundation for their production. Now, it is widely believed the OH-PBDEs in the food chain mainly come from the biosynthesis of ocean microorganisms rather than commercial PBDE products [ 12 ] In our previous investigation, OH/diOH-PBDEs were also detected in sea fish available in markets, indicating the potential risk of human exposure to these compounds [ 13 ].…”
Section: Introductionmentioning
confidence: 99%